Part-based tracking with cascaded regression of neighbours - Wang, Xiaomeng (2018)
Visual tracking aims to detect the location of a possibly moving target by extracting local appearance features and matching them between consecutive images to obtain accurate estimates of target location. Tracking of generic objects is one of the most active topics in computer vision. Despite the large body of work addressing this problem, robust visual tracking of generic objects is still a challenging problem, as the performance of a visual tracking algorithm is affected by many factors, such as non-rigid object deformation, partial or full occlusion of the target, illumination variation, scale variation, etc. Especially, many objects in the real world have a complex appearance and articulated structure. The combination of rigid motion and non-rigid object deformation results in complex appearance changes, making general object tracking a particularly hard problem.